2019
DOI: 10.3390/jcdd7010002
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Prevalence of Atrial Septal Defect and Its Associated Factors among Congenital Heart Disease Patients in Vietnam

Abstract: Atrial septal defect (ASD) is a non-physiologic communication between the two atria, allowing the shunt between systemic and pulmonary circulation. Data about ASD prevalence among congenital heart disease patients (CHD) in Vietnam are still scarce. We aim to assess the trends in the prevalence of ASD patients and associated factors among CHD patients. This was a cross-sectional study, with data collected from medical records from 1220 CHD patients in Da Nang hospital from 1 January 2010 to 31 December 2015. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…The most common CHDs diagnosed were VSD (31%), which is similar to reported cases in other countries [ 19 , 20 ]. ASD was the second most common CHD (23%), which is similar to a study by Xuan et al [ 21 ]. It was also the most common form of CHD which is frequently missed during childhood.…”
Section: Discussionsupporting
confidence: 89%
“…The most common CHDs diagnosed were VSD (31%), which is similar to reported cases in other countries [ 19 , 20 ]. ASD was the second most common CHD (23%), which is similar to a study by Xuan et al [ 21 ]. It was also the most common form of CHD which is frequently missed during childhood.…”
Section: Discussionsupporting
confidence: 89%
“…It was suggested that birth weights less than 2500 g, screening at 0–3 months and neonates with asphyxia or hypoxia had a diagnostic risk factor for ASD [17] , [18] . Individuals aged 10–40 years and females had a high risk of ASD compared to males aged 0–9 years [19] . Amongst the molecular factors, the genotype of the MTHFR gene (c.677C > T: CT or TT) was correlated with ASD [20] .…”
Section: Discussionmentioning
confidence: 92%
“…A subject with a CTD excluded individuals with an isolated VSD or ASD. Given high prevalence in the general population 47 , 48 , individuals with common, minor heart anomalies (VSD that closed spontaneously in infancy, ASD that closed spontaneously in infancy, persistent foramen ovale that closed spontaneously in infancy, or bicuspid aortic valve, in the absence of other malformations), were considered to be controls.…”
Section: Methodsmentioning
confidence: 99%